Topographies of security and the multiple spatialities of (conservation) power: Verticality, surveillance, and space-time compression in the bush. (November 2018) - Massé, Francis
Abstract: This article advances the analytic of topography to account for vertical and horizontal dimensions of space, power, and the ways in which they articulate with biophysical and political-ecological dynamics to (re)-shape socio-spatial and socio-natural relations. While commonly used to refer to the horizontal, vertical, and environmental features of a particular landscape, social scientists use the language of topography to understand the connections between spaces, processes, and power dynamics. I combine these literal and metaphorical understandings of topography to examine how multiple dimensions of space and power coalesce to protect certain bodies, police others, and secure the space within each move. In response to increases in commercial poaching, for example, conservation-security actors are increasingly going aerial to mobilise the vertical as a dimension of space and power to protect wildlife, neutralise those who threaten them, and ultimately secure conservation areas below. Verticality thus becomes important as both an empirical and analytical phenomenon that matters for understanding shifting power dynamics in contexts where actors seek to secure space and resources from perceived threats. But, the vertical does not exist on its own. It is in the interaction of the horizontal, vertical, and political-ecological dynamics of protected areas that conservation-related power-geometries are altered. A topographical analysis results in a nuanced understanding of how power and related security practices and technologies work to (re-)shape human environment and territorial relations. Highlights: I use a topographical approach to understand the dimensions of conservation power. Anti-poaching actors use aerial technologies and practices to secure conservation territories. The vertical articulates with the horizontal and political-ecological dynamics and practices. This tilts power geometries and bolsters protected areas as exclusionary enclosures. Topography shows nuances and interactions of different dimensions of space and power.